Development of Laban Notation Learning Design Based on Direct Instruction Model in Higher Education - Khaerah, Miftahul; Linda, Johar; Sumiani, Sumiani (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study's objective is to develop a Laban notation learning design based on the direct instruction model in dance notation courses. The research method used is Research and Development (R&D) with the 4-D Thiagarajan development model, which includes the stages of define, design, and development. This research was conducted at the Dance Study Program, Department of Performing Arts, Faculty of Arts and Design, Makassar State University. Data were collected through observation, questionnaires, literature studies, and expert validation. The results of the study indicate that based on the needs analysis, students have a high level of need for a more structured Laban notation learning design. The application of the direct instruction model is considered to be able to improve students' understanding of Laban notation. The Laban notation learning design based on direct instruction developed in this study produces a Semester Learning Plan (SLP) product. The results of expert validation show that the product meets the valid criteria, while the results of the trial show that this learning design is qualified and effective in improving students' understanding.